Formulation and Evaluation of Solid Lipid Nanoparticles Loading Erythromycin Ethylsuccinate by Heating Emulsification and Homogenization Methods - Mardiyanto Mardiyanto; Budi Untari; Ady Mara; Sadakata Sinulingga; Nirwan Syarif; Gustina Emilia Ningsih (Science and Technology Indonesia, 2022)
The pandemic period has caused antibiotics highly recommended to cure infections. The use of macrolide antibiotics has greatly increased recently due to outbreaks of diseases that attack the human respiratory tract all of part of the world. One member of the macrolide group is erythromycin ethyl succinate which has low solubility in water. Therefore, this study aims to convert erythromycin ethyl succinate into lipid nanoparticles in an attempt to increase solubility. The method for the formation of nanoparticles is heating emulsification and homogenization. The results obtained in the form of formula 1 (F1) showed the percent encapsulation of 85.688±0.30641. The physical properties were that it has a size of 398.9±1.4 nm, a PDI of 0.3895±0.0015, and zeta potential of -17.45±0.15 mV respectively. The stability was determined by an accelerated test by the influence of extreme temperature and mechanics affecting the stability of the particles as an indication of decreasing the pH and particle precipitation. The solubility of erythromycin ethyl succinate in the form of lipid nanoparticles was increased in a comparison with the pure substance of erythromycin ethyl succinate.